Development and laboratory evaluation of a competitive ELISA for serodiagnosis of Nipah and Hendra virus infection using recombinant Nipah glycoproteins and a monoclonal antibody - Zhu, Wenjun; Pickering, Bradley; Smith, Greg; Pinette, Mathieu; Truong, Thang; Babiuk, Shawn; Kobasa, Darwyn; Banadyga, Logan; Yang, Ming (Frontiers in Veterinary Science, 2023)
Nipah virus (NiV) and Hendra virus (HeV), of the genus Henipavirus, family Paramyxoviridae, are classified as Risk Group 4 (RG4) pathogens that cause respiratory disease in pigs and acute/febrile encephalitis in humans with high mortality. A competitive enzyme–linked immunosorbent assay (cELISA) using a monoclonal antibody (mAb) and recombinant NiV glycoprotein (G) was developed and laboratory validated with sera from experimental pigs, mini pigs and nonhuman primates. The test depends on competition between specific antibodies in positive sera and a virus–specific mAb for binding to NiV G. Based on 1199 negative and 71 NiV positive serum test results, the cutoff value was determined as 35% inhibition. The diagnostic sensitivity and specificity of the NiV cELISA was 98.58% and 99.92%, respectively. When testing sera from animals experimentally infected with NiV Malaysia, the cELISA detected antibodies from 14 days post-infection (dpi) and remained positive until the end of the experiment (28 dpi). Comparisons using the Kappa coefficient showed strong agreement (100%) between the cELISA and a plaque reduction neutralization assay (PRNT). Because our cELISA is simpler, faster, and gives comparable or better results than PRNT, it would be an adequate screening test for suspect NiV and HeV cases, and it would also be useful for epidemiological surveillance of Henipavirus infections in different animal species and humans without changing reagents.